Coping Strategies of Family Members of Hospitalized Psychiatric Patients - Phyllis M. Eaton; Bertha L. Davis; Pamela V. Hammond; Esther H. Condon; Zina T. McGee (Hindawi Limited, 2011)
This exploratory research paper investigated the coping strategies of families of hospitalized psychiatric patients and identified their positive and negative coping strategies. In this paper, the coping strategies of 45 family members were examined using a descriptive, correlational, mixed method research approach. Guided by the Neuman Systems Model and using the Family Crisis Oriented Personal Evaluation Scales and semistructured interviews, this paper found that these family members used more emotion-focused coping strategies than problem-focused coping strategies. The common coping strategies used by family members were communicating with immediate family, acceptance of their situation, passive appraisal, avoidance, and spirituality. The family members also utilized resources and support systems, such as their immediate families, mental health care professionals, and their churches.